2022
DOI: 10.1002/adpr.202100302
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical Birefringent Rib‐Channel Chirowaveguides for Quasicircularly Polarized Light Applications in Integrated Photonics

Abstract: Polarization in photonic‐integrated circuits (PICs) is governed by transverse electric (TE) and magnetic (TM) polarizations due to the planar structure of the chips. Therefore, all states of polarization (SOPs) other than TE and TM, in particular circular polarization, cannot be routed without modification across the chips. Herein, the realization of rib‐channel chirowaveguides supporting elliptically polarized guided modes by combining linear and circular birefringences as predicted by the coupled mode approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In our previous study, single-mode chirowaveguides have been characterized as elliptical birefringent devices. The degree of their polarization ellipticity is governed by the interplay between circular and linear birefringence [4]. In all our measurements, we never observed any dichroisms.…”
Section: Measurement Principlementioning
confidence: 43%
“…In our previous study, single-mode chirowaveguides have been characterized as elliptical birefringent devices. The degree of their polarization ellipticity is governed by the interplay between circular and linear birefringence [4]. In all our measurements, we never observed any dichroisms.…”
Section: Measurement Principlementioning
confidence: 43%
“…To test waveguiding in our materials, we must switch from making optical chiroptical measurements of banded spherulites normal to the radial growth direction 22,34,55 to make measurements along the radial growth direction, for example as in Scheme 2 53 . We have previously shown that the CR directed along twisted fibrils of polymers can be especially high at the very center of the polycrystalline ensemble where the fibers are parallel to the wavevector of light 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Optical fibers conventionally transmit linear polarization as transverse electric (TE) and transverse magnetic (TM) modes 41 . Waveguiding with circularly polarized modes is attractive for a variety of applications 50 and can be achieved with a chiral medium 51–53 . Though likely only marginally relevant to spherulitic growth of molecular crystals, helically twisted photonic bundles of silica fibers exploit their dissymmetry to control the orbital angular momentum of light 54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed the synthesis of a chiral ormosil precursor composed of an enantiopure binaphthyl unit covalently connected to a trialkoxysilane. Highly concentrated sols of this precursor in organic solvents, like dichloromethane or tetrahydrofuran, with PEG200 as an anti-cracking agent, can be coated as a thin film [2,3] and even micro-structured to produce rib optical waveguides [4]. The chirality of the gels introduces circular birefringence (CB) in the optical waveguides, leading to the formation of chirowaveguides [5].…”
Section: Introductionmentioning
confidence: 99%